Potensi Simpanan Karbon Pada Hutan Tanaman Mangium (Acacia mangium WILLD.) di KPH Cianjur Perum Perhutani Unit III Jawa Barat dan Banten - Anindita Roesyane; Bambang Hero Saharjo (Institut Pertanian Bogor, 2011)
One of the best solution to reduce the increasing of carbiondioxide is keeping the forest and its ecosystems sustainably. It should be done because the forest could store the carbon stock at high level capacity. The research purposed to calculate the above ground carbon stock of planted A.mangium. Planted A.mangium in the year 2002 and 2004 used for calculation. Research done during April to May 2010 ath KPH Cianjur, State Own Company Perhutani Unit III, West Java and Banten. Data collecting through plot establishment in the field that was 20 m x 20 m for trees biomass and 2 m x 2 m sub-plot for litter and understorey. Results of research shown that the carbon stock of A.mangium planted in the year was 43.30 ton/ha while planted in the year 2004 was 27.70 ton/ha.